1998
DOI: 10.1242/jcs.111.22.3311
|View full text |Cite
|
Sign up to set email alerts
|

Aryl-hydrocarbon receptor is an inhibitory regulator of lipid synthesis and of commitment to adipogenesis

Abstract: The aryl-hydrocarbon receptor (AhR) is a ligand-dependent transcription factor that mediates the biological effects of 2,3,7, 8-tetrachlorodibenzo-p-dioxin (TCDD). In mouse embryo fibroblasts, TCDD activates expression of multiple genes, including CYP1B1, the predominant cytochrome P450 expressed in these cells. Here, we analyze constitutive functions of the AhR in primary mouse embryo fibroblasts (MEFs) and spontaneously immortalized MEF cell lines derived from wild-type (WT) C57BL/6 mice and also from congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…AhR-null mouse embryonic fibroblasts (MEF), on passaging in culture, acquire a senescent phenotype earlier than wild type cells [ 28 ] and have reduced proliferation potential [ 48 ]. Flow cytometry and cytological staining for SA-β-Gal indicated that, upon passage in culture, AhR-null MEFs acquired higher levels of senescence than AhR+/+ MEFs (significant after passage 3, P3) ( Figure 6A – 6C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AhR-null mouse embryonic fibroblasts (MEF), on passaging in culture, acquire a senescent phenotype earlier than wild type cells [ 28 ] and have reduced proliferation potential [ 48 ]. Flow cytometry and cytological staining for SA-β-Gal indicated that, upon passage in culture, AhR-null MEFs acquired higher levels of senescence than AhR+/+ MEFs (significant after passage 3, P3) ( Figure 6A – 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…AhR modulates senescence in different cell types and organs, including mesenchymal embryonic fibroblasts [ 28 ]. Using passaging as a model for aging in culture, we found that MEFs from AhR−/− mice are more susceptible to senescence as determined by higher levels of SA-β-Gal, p16 Ink4a and p21 Cip1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary studies with HL60 and HEL cell lines showed that the differentiation from monocytes to macrophages with phorbol esters required the transcriptional activation of AHR ( Hayashi et al, 1995 ). Moreover, experiments performed to differentiate AHR +/+ and AHR −/− mouse embryonic fibroblasts (MEFs) to adipocytes revealed that AHR deficiency impairs the differentiation process, suggesting that AHR could be an early regulator of adipogenesis ( Alexander et al, 1998 ). Moreover, the accumulation of TCDD in adipose tissue induces an effect on oxidative stress enzymes in both adipocytes and liver, exacerbating oxidative stress ( Kern et al, 2002 ).…”
Section: Aryl Hydrocarbon Receptor Role In Pluripotency and Different...mentioning
confidence: 99%
“…were the first to provide evidence of a link between AhR activation by TCDD and energy balance [ 110 ]. Following this, several studies demonstrated the inhibitory action of TCDD on the synthesis of fatty acids in liver and adipose tissues [ 111 , 112 ], gluconeogenic enzymes such as G6Pase and PEPCK [ 113 ], and adipogenesis [ 114 ]. In this context, it has been reported that mice expressing a high constitutively active form of AhR spontaneously developed hepatic steatosis, characterized by high amounts of fatty acid import, suppressed fatty acid oxidation, and increased oxidation and mobilization of peripheral fat storage [ 115 ].…”
Section: The Role Of Ahr/cyp1a1 Pathway In Glucose Homeostasis and In...mentioning
confidence: 99%